2001
DOI: 10.1046/j.1439-0450.2001.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Products of Fourth-Stage Larvae of Oesophagostomum dentatum Induce Proliferation in Naive Porcine Mononuclear Cells

Abstract: Infection of pigs with Oesophagostomum dentatum is a major cause of economic losses in pig productions. Whether infection with this nematode results in a protective immunity is still in debate and information about immune-modulating properties of O. dentatum are lacking. The present study investigated the question whether products of O. dentatum larvae modulate the proliferative response of porcine blood mononuclear cells (poMNC) in vitro. The poMNC of naïve and O. dentatum-infected pigs were cultured for 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In addition, somatic extracts of and supernatants from in vitro maintenance cultures of Oe. dentatum L4s have been shown to induce the proliferation of porcine mononuclear cells in vitro (310), which supports the hypothesis that L4-specific proteases play an active role in the modulation of the host's immune response (302)(303)(304). The results from a recent study (206) showed also that a high proportion (27-32%) of transcripts encoding protein kinases and phosphatases were common among all developmental stages of Oe.…”
Section: Understanding Nematodes Of Socioeconomic Importance Through supporting
confidence: 58%
“…In addition, somatic extracts of and supernatants from in vitro maintenance cultures of Oe. dentatum L4s have been shown to induce the proliferation of porcine mononuclear cells in vitro (310), which supports the hypothesis that L4-specific proteases play an active role in the modulation of the host's immune response (302)(303)(304). The results from a recent study (206) showed also that a high proportion (27-32%) of transcripts encoding protein kinases and phosphatases were common among all developmental stages of Oe.…”
Section: Understanding Nematodes Of Socioeconomic Importance Through supporting
confidence: 58%
“…Indeed, unresponsiveness of antigen‐specific T cells is described during helminth infections . On the other hand, when PBMC of lungworm infected cattle were stimulated with whole worm homogenate, an increased proliferation has been shown and studies using porcine and ovine PBMC demonstrated a clear and significant proliferative response towards helminthic infections . However, mentioned studies used proteins derived from parasite homogenates or secretory products of larvae, and thus containing a mixture of protein and nonprotein components in contrast to a single recombinant protein.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, O. dentatum L4s are known to evoke immunological reactions that result in the encapsulation of the larvae in nodules with aggregations of neutrophils and eosinophils (58,71). In addition, somatic extracts of and supernatants from in vitro maintenance cultures of O. dentatum L4s have been shown to induce the proliferation of porcine mononuclear cells in vitro (72). These observations suggest an active role for L4-specific proteases in the modulation of the host’s immune response, which (as proposed for other biological systems) could consist of: (i) the direct digestion of antibodies (68); (ii) cleavage of cell-surface receptors for cytokines (73) and/or (iii) direct lysis of immune cells (74).…”
Section: Discussionmentioning
confidence: 99%